Effects of functional group on the mechanical properties of PA6/SiO2 composites. Issue 3 (8th October 2013) - Liu, Juan; Yi, Hongling; Lin, Heng; Wei, Ting; Zheng, Baicun
<x xml:space="preserve">Abstract</x> The polyamide‐6 materials were mixed with nano‐silica modified by γ‐glycidoxypropyltrimethoxysilane (GPS) via a melt blending process. The idea was to study the correlation between content of GPS and PA6/silica interfacial interactions as well as mechanical properties of PA6/silica composites. The epoxy groups in GPS could react with –COOH and –NH2 in PA6 to produce the covalent bond and hydrogen bonding based on FTIR chart, TG analysis, and TEM analysis results. The DSC results show that nanosilica could encourage the formation of the hydrogen bonded structure of the α‐PA6 crystals. However, the over GPS could confine the motion of polyamide‐6 and decrease the generation of α‐PA6 crystals resulted the decrease of mechanical properties. So the amount of epoxy groups grafted on nano‐silica has a threshold effect on strength of PA6. POLYM. COMPOS., 35:435–440, 2014. © 2013 Society of Plastics Engineers